Food fraud - Grace, Delia (Elsevier, 2019)
Food fraud implies deception for gain using food. We summarise types of food fraud and explain why they matter to food and nutrition security. The most common types of food fraud and rough estimates of their prevalence are given. We highlight examples from low and middle income countries. Prevention is discussed, and conclusions drawn.